A phase II−III trial of olesoxime in subjects with amyotrophic lateral sclerosis. (21st January 2014) - Lenglet, T.; Lacomblez, L.; Abitbol, J. L.; Ludolph, A.; Mora, J. S.; Robberecht, W.; Shaw, P. J.; Pruss, R. M.; Cuvier, V.; Meininger, V.; ,; Meininger, Vincent; et al.
<x xml:space="preserve">Abstract</x> Background and purpose To assess the efficacy and safety of olesoxime, a molecule with neuroprotective properties, in patients with amyotrophic lateral sclerosis (ALS) treated with riluzole. Methods A double‐blind, randomized, placebo‐controlled, multicenter trial of 18 months' duration was conducted in 512 subjects, with probable or definite ALS and a slow vital capacity (SVC) ≥70%, receiving 330 mg olesoxime daily or matching placebo and 50 mg riluzole twice a day in all. The primary intention‐to‐treat (ITT) outcome analysis was 18 months' survival. Secondary outcomes were rates of deterioration of the revised ALS functional rating scale (ALSFRS‐R), focusing on the 9‐month assessment, SVC and manual muscle testing. Blood levels, safety and tolerability of olesoxime were also assessed. Results At 18 months, 154 of the 512 ITT patients had died (79 of 253 placebo, 75 of 259 olesoxime). Estimated overall survival according to Kaplan–Meier analysis was 67.5% (95% CI 61.0%–73.1%) in the placebo group and 69.4% (95% CI 63.0%–74.9%) in the olesoxime group; hence survival was not significantly different between treatment arms (P = 0.71, stratified bulbar/spinal log‐rank). The other efficacy end‐points evaluated were also negative, with the exception of a small difference in ALSFRS‐R global score at 9 months in favor of olesoxime but not sustained after 18 months' treatment nor evident in either the stratified bulbar or spinal subpopulations. Treatment did not raise any safety concerns. Conclusions Olesoxime, although well tolerated, did not show a significant beneficial effect in ALS patients treated with riluzole.